Analysis of Constitutional Court Decision Number 85/PUU-XIV/2016 Regarding Tender Rigging Practices - Adliakbar, Adliakbar; Ramadhan, Muhammad (IHSA Institute, 2025)
In essence, tender rigging is one form of conspiracy prohibited by Law Number 5/1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and is also the case most often processed by the KPPU. However, both theoretically and practically, it raises problems, namely because of the biased interpretation of the phrase